Creation of a Framework for Railway Timetable Optimization Criteria - Schittenhelm, Bernd (Proceedings from the Annual Transport Conference at Aalborg University, 2011)
During the last years, much effort has been put into developing mathematical models for timetable creation. All models need an objective function which describes criteria used to optimize and evaluate a timetable. In an attempt to find a Danish list of prioritized railway timetable evaluation criteria, this paper presents the five most important evaluation criteria from the 5 most important Danish railway timetable stakeholders. The criteria are grouped according to overall subjects and a first overview of the prioritization is given. From the criteria descriptions a series of indicators are deduced. This forms the basis for a decision process for finding a common accepted list of prioritized timetable evaluation criteria. This decision process will be accomplished on one or two decision making workshops. A reduction from 13 stated potential timetable evaluation criteria to between 4 and 6 is needed. To make the decision making process as accessible and transparent to the stakeholders as possible the SMARTER technique will be applied. A short description of the technique is given. The deduced indicators for each remaining criterion must also be ranked. Since some of the indicators are not easily quantifiable the “Direct Ranking” methodology will be used for this step in the process. The methodology is briefly described. Hereby the roadmap for a first common Danish list of prioritized railway timetable evaluation criteria is given.